(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Research aims to determine how the Sarajevo Film Festival affects on the tourist satisfaction of the Sarajevo as a tourism destination. One of the goals is to provide, on the basis of survey results, recommendations for a more efficient use of the Sarajevo Film Festival as a factor of event tourism in creating an authentic and recognizable tourist product of Sarajevo. The research part of the work analyzes the influence of the Sarajevo Film Festival on the tourist satisfaction of the Sarajevo as a tourism destination and the impact of the Sarajevo Film Festival on the improvement of the tourist offer of the city of Sarajevo. The contribution of this research is reflected in the promotion of enormous cultural significance of the Festival, as one of the most important tourist projects of the region and beyond and in strengthening the image of the country, in particular the city of Sarajevo.